The contributions of the tissue inhibitor of metalloproteinase-1 genotypes to triple negative breast cancer risk - Chang, Wen-Shin (Biomedicine (Taipei), 2016)
The tissue inhibitors of metalloproteinases (TIMPs) are a family of multifunctional proteins which have been shown to be upregulated in various types of cancers. However, the contribution of TIMPs in breast cancer is not fully understood, not to mention triple negative breast cancer (TNBC). This study’s aim was to evaluate the contribution of TIMP-1 rs4898, rs6609533, and rs2070584 genotypes to the risk of breast cancer, especially the subtype of TNBC. The contributions of these TIMP-1 genotypes to cancer risk were examined among 1232 breast cancer patients and 1232 healthy controls, and several clinicopathologic factors were also analyzed. The results showed that the percentages of CC, CT, and TT of TIMP-1 rs4898 were differentially distributed at 28.5%, 33.1% and 38.4% in the breast cancer patient group and 34.5%, 41.0% and 24.5% in the control group, respectively (P for trend = 7.99*10(-13)). It was also found that the CC genotype carriers were of increased risk for breast cancer (odds ratio = 1.90, 95% confidence interval = 1.55-2.33, P = 0.0001) than the TT genotype carriers. In addition, we analyzed the allelic frequency distributions of all three TIMP-1s, and the results showed that the C allele of TIMP-1 rs4898 contributes to an increase in breast cancer susceptibility (P = 2.41*10(-12)). On the other hand, there was no difference found in the distribution of genotypic or allelic frequencies among the patients and the controls for TIMP-1 rs6609533 and rs2070584. Thus, it is our conclusion that the CC genotype of TIMP-1 rs4898 compared to the TT wild-type genotype may increase the risk for breast cancer, especially TNBC in Taiwan, and may serve as an early detective and predictive marker.